When is a maternal effect adaptive? - Marshall, D; Uller, T (2007)
Maternal effects have become an important field of study in evolutionary ecology and there is an ongoing debate regarding their adaptive significance. Some maternal effects can act to increase offspring fitness and are called 'adaptive maternal effects'. However, other maternal effects decrease offspring fitness and there is confusion regarding whether certain maternal effects are indeed adaptive or merely physiological inevitabilities. Here we suggest that the focus on the consequences of maternal effects for offspring fitness only and the use of 'snapshot' estimates of fitness have misdirected our effort to understand the evolution of maternal effects. We suggest that selection typically acts on maternal effects to maximise maternal rather than (or in addition to) offspring fitness. We highlight the importance of considering how maternal effects influence maternal fitness across a mother's lifetime and describe four broad types of maternal effects using an outcome-based approach. Overall, we suggest that many maternal effects will have an adaptive basis for mothers, regardless of whether these effects increase or decrease survival or reproductive success of individual offspring. © 2007 The Authors.